The Factors Associated with Risk and Time Preferences: Evidence from Australian Data - Angelita Titis Pertiwi (Universitas Brawijaya, 2022)
Risk and time preferences are crucial to economic growth because they can influence people's decisions about saving and investing. These preferences may partially explain inequality, the reason why the poor will always be poor. The aims of this study is to investigate the potential factors contributing to the heterogeneity of risk-taking and patient behavior in Australia using cross-sectional data from 2019. This investigation looks for the association between risk-taking and patient behavior and sociodemographic characteristics using the OLS (Ordinary Least Squares) assessment. Age, gender, education, socio-economic index, household formations, indigenous individuals, spoken language at home for daily conversation, and country of birth are the variables. The key finding in terms of patience is that people with higher levels of education, people who live in areas with higher levels of socio-economic advantage, and individuals who live in a home with couple-family have higher levels of time preference. Moreover, persistence is adversely related with native endlessly individuals brought into the world in principally English-talking foundation nations. As far as hazard inclinations, the primary outcome is that ladies are more gamble unwilling than men. Besides, risk-taking way of behaving is decidedly related with individuals living in regions encountering lower levels of financial drawback, individuals living in a solitary parent family, and individuals brought into the world in basically non-English talking foundation nations.